2009
DOI: 10.1111/j.1755-3768.2009.4351.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating bone marrow‐derived endothelial precursor cells contribute to neovascularization in diabetic epiretinal membranes

Abstract: Purpose Role of vasculogenesis, recruitment and differentiation of circulating bone marrow‐derived endothelial precursor cells into mature endothelium, in proliferative diabetic retinopathy (PDR) remains undefined. We investigated the presence of bone marrow‐derived endothelial precursor cells and the expression of the chemotactic pathway SDF‐1/CXCL12?CXCR4 in PDR epiretinal membranes. Methods Membranes from 8 patients with active PDR and 9 patients with inactive PDR were studied by immunohistochemistry using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…In T2DM patients with DR, circulating angiopoietic cells as EPCs, and mature EPCs had different regulations in PDR depending on each individual's macrovascular comorbidities (Brunner et al, 2011). Recent findings in diabetic patients have corroborated gathered experimental data, demonstrating that BMderived CD133+ EPCs, as well as, CD14+ monocytes could be mobilized to diabetic epiretinal membranes, contributing to vasculogenesis in PDR (Abu El-Asrar et al, 2011). Taken together, these data strengthen the importance of EPCs in the development of human PDR, highlighting the crucial role played by both the local retinal and the systemic environment.…”
Section: Epcs and Diabetic Retinopathy (Dr)supporting
confidence: 68%
“…In T2DM patients with DR, circulating angiopoietic cells as EPCs, and mature EPCs had different regulations in PDR depending on each individual's macrovascular comorbidities (Brunner et al, 2011). Recent findings in diabetic patients have corroborated gathered experimental data, demonstrating that BMderived CD133+ EPCs, as well as, CD14+ monocytes could be mobilized to diabetic epiretinal membranes, contributing to vasculogenesis in PDR (Abu El-Asrar et al, 2011). Taken together, these data strengthen the importance of EPCs in the development of human PDR, highlighting the crucial role played by both the local retinal and the systemic environment.…”
Section: Epcs and Diabetic Retinopathy (Dr)supporting
confidence: 68%
“…The prevalence of cells staining with microglial markers near the vasculature led these authors to coin the phrase "microvascular perivasculitis." This is not unlike the perivascular CD14-positive monocyte/macrophage staining observed in ERM removed from patients with active PDR [48], in that there is no direct evidence that the cells observed by Zeng and coworkers were actually retinal microglia. Thus, we can only conclude that monocytes/macrophages are coincident with the focal pathologies that occur in DR.…”
Section: Microglial Activation In Diabetic Retinopathymentioning
confidence: 53%
“…Additionally, it is now known that bone marrow-derived resident monocytes/ macrophage cells, called hyalocytes, occupy the periphery of the vitreous cavity, and it was presumed that these are the cells that are present and causal in ERM formation [47]. More recently, Abu El-Asrar and colleagues studied ERM from patients with active and inactive PDR and concluded that vessel-associated cells included bone marrow-derived CD133-positive endothelial precursor cells as well as CD14-positive monocytes that may have also originated from the bone marrow [48]. These cells were more prevalent in samples from patients with active PDR.…”
Section: Microglial Activation In Diabetic Retinopathymentioning
confidence: 99%
“…On the other hand, Dll4/Notch signaling controls vessel sprouting and branching, and inhibition of DLL4 showed reduced pathological neovessels in OIR (35). Moreover, CXCR4, a receptor for SDF-1 signaling, showed increased expression in diabetic epiretinal membranes (36), and inhibition of CXCR4 reduces the laser-induced CNV lesion sizes and leakage in rats (37). Together these findings are consistent with our data of miR-150, a suppressor of Fzd4, Dll4, and Cxcr4, protecting against OIR.…”
Section: Discussionmentioning
confidence: 98%